Niedopuszczalność oficjalnego uznania w Rzeczypospolitej Polskiej rodzicielstwa osób tej samej płci. Glosa do wyroku Naczelnego Sądu Administracyjnego z dnia 28 lutego 2024 r., II OSK 1303/21 - Bucoń, Paweł (PRAWO i WIĘŹ, 2025)
In its judgment of 28 February 2024, the Supreme Administrative Court ruled that it was inadmissible to enter the names of persons of the same sex as the parents of the holder of the identity card in the identity card, i.e. in accordance with the content of the birth certificate issued by an authority of a foreign country. The commented judgment is in compliance with the line of case law of the Supreme Administrative Court established by resolution II OPS 1/19 of 2 December 2019, in which it was ruled that it was inadmissible to transcribe a foreign birth certificate indicating persons of the same sex as the parents of the child. The author of the commentary shares the position of the Supreme Administrative Court on the inadmissibility of denying the right of a Polish citizen to receive an identity card solely because the foreign birth certificate indicated persons of the same sex as the parents. In such a situation, the body issuing the identity card is obliged to enter the name of the biological parent, while the space intended for the name of the other parent should remain empty.